Verbatim and Semantic Imitation in Indexing Resources on the Web: A Fuzzy‐trace Account of Social Tagging. Issue 1 (29th August 2014) - Seitlinger, Paul; Ley, Tobias; Albert, Dietrich
Summary Social tagging is a widespread phenomenon on the Web allowing users to tag resources, such as photos, by freely chosen labels. Imitation of other users' tagging behavior is deemed to increase the inter‐individual consistency of tag assignments. Both verbatim and semantic mechanisms have been proposed where the first case suggests reuse of the exact words and the second reuse of the concept without necessarily the word form. Here, we present a multinomial model of assigning tags that integrates these perspectives. On the basis of the fuzzy‐trace theory, the model includes separate parameters for the retrieval of verbatim and gist traces of encountered tags. Results of two experiments demonstrate that both types of memory traces contribute substantially and independently to tag productions. We conclude that the imitation of tags may be explained within one fuzzy‐trace framework that contributes to our understanding of emergent phenomena in social information systems. Copyright © 2014 John Wiley & Sons, Ltd.